IMPROVING READING COMPREHENSION USE QUIZIZZ APPLICATION AND COGNITIVE STYLE - Dewi, Emilia Purnama; Tahrun; Masagus Firdaus (Universitas PGRI Palembang, 2025)
This study explores the impact of the Quizizz application and visualizer-verbalizer cognitive styles on students' reading comprehension. The research aims to determine whether interactive learning tools like Quizizz can improve students' reading comprehension by considering their cognitive preferences. The issues addressed in this study include (1) students perceiving English as a challenging subject, (2) weak reading comprehension skills in descriptive texts, (3) limited mastery of English grammar, (4) disengagement with conventional teaching methods, and (5) the need for interactive tools to boost engagement and comprehension. The study specifically examines the influence of the Quizizz application and cognitive styles on the reading comprehension of seventh-grade students. Employing a 2 x 2 factorial design, the research focuses on two independent variables: the use of Quizizz and cognitive styles (visualizer vs. verbalizer). The findings reveal that the Quizizz application significantly enhances students' reading comprehension. Furthermore, the interaction between the Quizizz application and cognitive styles suggests that personalized digital tools can improve student engagement and comprehension, offering valuable insights for future English language teaching strategies.